Stakeholders matter a new paradigm for strategy in society - Sachs, Sybille. (Business, value creation, and society., 2011)
"The dominant shareholder-value model has led to mismanagement, market failure and a boost to regulation, as spectacularly demonstrated by the events surrounding the recent financial crisis. Stakeholders Matter challenges the basic assumptions of this model, in particular traditional economic views on the theory of the firm and dominant theories of strategic management, and develops a new understanding of value creation away from pure self-interest toward mutuality. This new 'stakeholder paradigm' is based on a network view, whereby mutuality enhances benefits and reduces risks for the firm and its stakeholders. The understanding of mutual value creation is operationalized according to the license to operate, to innovate and to compete. The book develops a vision for a strategy in society in which, rather than the invisible hand of the market, it the visible hands of the firm and the stakeholders that lead to an overall increase in the welfare of society"--